2010
DOI: 10.1080/13662711003633496
|View full text |Cite
|
Sign up to set email alerts
|

Nordic City Regions in the Creative Class Debate—Putting the Creative Class Thesis to a Test

Abstract: The Nordic countries have a quite different urban structure and social systems than the USA. Denmark, Finland, Norway and Sweden may then constitute a critical test of the empirical reach of Richard Florida's much cited creative class thesis beyond its empirical basis in the USA. This paper employs comparative statistics to examine the importance of the quality of place in attracting members of the creative class to Nordic city regions, and it analyses the role of the creative class for regional economic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 17 publications
3
65
0
3
Order By: Relevance
“…Empirical flndings also testify that higher growth rates correlate with high concentrations of the creative class (Andersen et al, 2010;Boschma and Fritsch, 2009;Clifton, 2008;Hansen, 2007). Taking an outlook on Europe, it is indisputable that economic growth has taken place in the areas where creative and/or human capital is concentrated.…”
Section: Skills and Human Capitalmentioning
confidence: 90%
“…Empirical flndings also testify that higher growth rates correlate with high concentrations of the creative class (Andersen et al, 2010;Boschma and Fritsch, 2009;Clifton, 2008;Hansen, 2007). Taking an outlook on Europe, it is indisputable that economic growth has taken place in the areas where creative and/or human capital is concentrated.…”
Section: Skills and Human Capitalmentioning
confidence: 90%
“…It turns out that labour productivity growth is positively affected by the presence of the creative class, which however does not affect employment dynamics. Finally, Andersen et al (2010), in a simple partial correlation framework applied to four Nordic countries (Denmark, Finland, Norway and Sweden), show that the creative class is positively correlated with employment growth only for the case of the large city regions, while it results not significant once all regions are considered; the opposite outcomes are found for the schooling measure.…”
mentioning
confidence: 78%
“…Referring to the European context, graduates are found to enhance employment growth in the German and Dutch regions (Boshma and Fritsch, 2009) and in the Nordic countries regions (Andersen et al, 2010); evidence in favour of creativity as a driver of labour growth is provided by Marlet and Van Woerkens (2007) and Boshma and Fritsch (2009) for the Netherlands. In some studies (Marlet and Van Woerkens, 2007;Mellander and Florida, 2011) a relevant role is also found for the Bohemians; their presence can act as an attractor for highly educated people who tend to prefer working in more open, diverse and tolerant environments.…”
mentioning
confidence: 99%
“…Concrete aspects include, but are not limited to, taking bold steps to stimulate the commercialization of knowledge and creating a supportive environment conducive to sustainable financial investments (Nilsson and Etelä, 2006; see also Power et al, 2006). Studies have revealed that, despite a number of strengths like 'creative approaches to education' and 'excellence models for incubation and cluster development', the Nordic countries still suffer from a series of inadequacies ranging from a fragmented policy landscape to small domestic markets and cities (Fleming and NilssonAndersen, 2007; see also Andersen et al, 2010).…”
Section:  Connecting Firms Within Ccis With Other Industries;mentioning
confidence: 99%